Examining The Underlying Variables Between Price and Subscription Continuance of Netflix’s Subscribers in Jakarta - Galingging, Jesusha Glory Anemone; Niha, Irma Shafika; Nurfaiza, Nazia; Pangaribuan, Christian Haposan (Eligible : Journal of Social Sciences, 2023)
Understanding the underlying variables that influence willingness to purchase certain products is crucial as it helps businesses to make better decisions to market their products. This study focuses on the Video on Demand industry and aims to explore the relationship between Netflix Subscription Continuance and Price that is mediated by two variables, namely Perceived Quality and Content. This research addresses the reason behind the phenomenon of customers’ decision to keep subscribing to Netflix despite the fact that there is an increasing price on the platform. The data for this paper is obtained from 111 Netflix subscribers in Jakarta who once and/or continue subscribing to Netflix, while the results are analyzed using SmartPLS. The findings of this research reveal that the direct relation between Price and Subscription Continuance is not significant. However, the indirect relationship that is mediated by Perceived Quality and Content both indicate significant relationships. This study discloses that improving Content and Perceived Quality will result in an increase in Subscription Continuance of Netflix.